2019
DOI: 10.3389/fnagi.2019.00218
|View full text |Cite
|
Sign up to set email alerts
|

Cycling and Spatial Navigation in an Enriched, Immersive 3D Virtual Park Environment: A Feasibility Study in Younger and Older Adults

Abstract: Background Cognitive decline is a significant public health concern in older adults. Identifying new ways to maintain cognitive and brain health throughout the lifespan is of utmost importance. Simultaneous exercise and cognitive engagement has been shown to enhance brain function in animal and human studies. Virtual reality (VR) may be a promising approach for conducting simultaneous exercise and cognitive studies. In this study, we evaluated the feasibility of cycling in a cognitively enriched a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 58 publications
1
39
0
Order By: Relevance
“…There are several previous examples of studies that have involved viewings of natural environments by VR technology for various therapeutic purposes including: improving muscle strength and balance [28]; improving cognitive function [28,29]; reducing anxiety and agitation [30], and improving engagement, apathy, and mood states [31] in people with dementia; and improving motivation to exercise and mental wellbeing [32]. A recent study explored the acceptability of VNEs for people with memory loss at memory cafes [33].…”
Section: Use Of Vr Natural Environments In the Elderly Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several previous examples of studies that have involved viewings of natural environments by VR technology for various therapeutic purposes including: improving muscle strength and balance [28]; improving cognitive function [28,29]; reducing anxiety and agitation [30], and improving engagement, apathy, and mood states [31] in people with dementia; and improving motivation to exercise and mental wellbeing [32]. A recent study explored the acceptability of VNEs for people with memory loss at memory cafes [33].…”
Section: Use Of Vr Natural Environments In the Elderly Populationmentioning
confidence: 99%
“…A recent study explored the acceptability of VNEs for people with memory loss at memory cafes [33]. Some of these studies have involved activities like kayaking [28], bicycling [29,32], or interacting with objects present in the VE through hand and arm movements [31]. However, a rather small number of the previous studies have regarded the potential therapeutic effects of exposure to natural environments.…”
Section: Use Of Vr Natural Environments In the Elderly Populationmentioning
confidence: 99%
“…Htut et al found that a virtual reality video-game-based exercise, which is less beneficial than standard physical activity in assessments of physical ability but better than controls, can also simultaneously improve cognitive function [ 83 ]. Integration of virtual environments with existing exercise modalities, such as stationary cycling, has been found to be appropriate for younger and older individuals alike, while being rated as enjoyable by users, promoting long-term adherence to the exercise program [ 81 , 84 , 85 ].…”
Section: Applications Of Virtual Reality In Cognitive Disorder Tesmentioning
confidence: 99%
“…Many VR applications may benefit older adults, particularly. VR can be used for virtual exercise programs (Sakhare, Yang, Stradford, et al, 2019;Bruun-Pedersen, Serafin, Maculewicz, et al, 2016), which can have similar benefits as traditional workout techniques (Plante, Aldridge, Bogden, & Hanelin, 2003) with additional benefits for mood, and can be more enjoyable and motivating than traditional techniques (Molina, Ricci, de Moraes, & Perracini, 2014;Plante et al, 2003). VR has been used with older adults for easing chronic pain (Hoffman et al, 2004), training gait and balance (Hoffman et al, 2004), and training motor control (De Bruin, Schoene, Pichierri, & Smith, 2010).…”
Section: Introductionmentioning
confidence: 99%